PEMODELAN DAN ANALISIS KEUNTUNGAN PADA USAHA AGEN PENTOL KABUL DI WONOREJO MENGGUNAKAN PENDEKATAN MATEMATIKA EKONOMI - Riffat Haziq; Dessy Boegiyati (Cashless : Journal of Sharia Finance and Banking, 2026)
UMKM play a significant role in Indonesia’s economy, including in the culinary agency-based business sector such as Pentol Kabul Agencies. However, many business owners still do not apply quantitative analysis in decision-making, particularly in understanding the relationship between costs, revenue, and profit. This study aims to develop mathematical models of the cost function, revenue function, and profit function for a Pentol Kabul agency business, as well as to analyze its profit level and Break-Even Point (BEP). The research employed a quantitative descriptive approach using a case study method on a Pentol Kabul agency located in Pasuruan Regency. Data were collected through interviews, observations, and documentation of business sales records. The analysis was conducted by formulating the total cost (TC), total revenue (TR), and profit (π) functions, followed by break-even analysis and sensitivity analysis regarding changes in cost of goods sold and selling prices. The results indicate that the cost function is TC(Q) = 225,000 + 35,000Q, the revenue function is TR(Q) = 40,000Q, and the profit function is π(Q) = 5,000Q − 225,000. At the actual sales volume of 150 packs per week, the business generates a profit of IDR 525,000 per week. Furthermore, the break-even point is achieved at a sales volume of 45 packs per week. These findings demonstrate that the application of economic mathematics can assist MSME owners in understanding business conditions more systematically and support more rational business decision-making.